Academia's Breath: Oxygenating Academia One Creative, Embodied Breath at a Time - Sarah Crinall (University of Johannesburg, 2023)
Australia is one colonised country in the Global South trying to live differently with our 'morbid symptoms'. The global South's Academy has a neoliberal coating that hopefully can be perforated - even if slightly - with intentional and unintentional shifts in how we do academia that allow oxygen into scholarship with some different scholarly processes. The health of the planet, where we are inextricably linked to planetary health, calls for care within and between academic bodies - (non)human bodies, water bodies and bodies of knowledge. I have examined some old blogposts playfully to understand creative blogging as one hopeful way toward an academic sustenance. This entry listens like a record to select blog posts through the voices of feminist black scholars and First Nations informed expertise in the post qualitative, new material turn. By re-experiencing and expressing the sustaining nature of academia to date there are some practical possibilities for an everyday, mothering, emerging academic to do academia differently. Entangled with the unceded lands and waters of Australia's First Nation people's - the Boonwurrung / Bunurong - a moment of everyday, academic emergence asks - an academia that plays out one creative, embodied, oxygenated breath at a time - how would you do that?